2016
DOI: 10.1371/journal.pone.0161491
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis: Identification of Common Mir-145 Target Genes that have Similar Behavior in Different GEO Datasets

Abstract: BackgroundMicroRNAs, which are small regulatory RNAs, post-transcriptionally regulate gene expression by binding 3'-UTR of their mRNA targets. Their deregulation has been shown to cause increased proliferation, migration, invasion, and apoptosis. miR-145, an important tumor supressor microRNA, has shown to be downregulated in many cancer types and has crucial roles in tumor initiation, progression, metastasis, invasion, recurrence, and chemo-radioresistance. Our aim is to investigate potential common target ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…We have also demonstrated miR-145-3p is downregulated in cancer tissues and acts as an antitumor miRNA in bladder, lung, and prostate cancers by targeting several oncogenic genes ( 10 , 11 , 31 ). Previous studies demonstrated that several oncogenic genes were regulated by miR-145-5p in several types of cancers ( 32 34 ). There are few studies for target genes by miR-145-3p regulation in cancer cells, including HNSCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…We have also demonstrated miR-145-3p is downregulated in cancer tissues and acts as an antitumor miRNA in bladder, lung, and prostate cancers by targeting several oncogenic genes ( 10 , 11 , 31 ). Previous studies demonstrated that several oncogenic genes were regulated by miR-145-5p in several types of cancers ( 32 34 ). There are few studies for target genes by miR-145-3p regulation in cancer cells, including HNSCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in the latter study, we demonstrated that miRNA-145 is a critical regulator of this phenotypic switching. Importantly, miRNA-145 has been identified as a tumour suppressor miRNA, confirming an association with DNA damage in a variety of cancer cell-types (17,18).…”
Section: Discussionmentioning
confidence: 79%
“…Full texts of the associated articles were evaluated for details on patient selection, demographics, sampling and RNA analysis. Six out of 16 were further excluded as the median centered across samples was not zero 27 and final analysis was carried out on 10 datasets (Table 2). Processing of microarray dataset .…”
Section: Methodsmentioning
confidence: 99%